Quantitative analysis of guided wave in dielectric logging through numerical simulation - Wang, Bin; Huang, Zixuan; Xing, Lanchang; Lao, Liyun; Wei, Zhoutuo; Ge, Xinmin (IEEE, 2020)
A good knowledge of the electromagnetic (EM) wave propagation behaviors in dielectric logging (DL) and borehole radar (BHR) surveying is critically important for the optimization of tool design and implementation, and interpretation of the acquired logging data, as well as understanding the influences of the dielectric permittivity and conductivity of the formation on the EM waves. This letter reported a novel method for the numerical simulation and analysis of the guided wave (GW) propagating along a metallic pipe in a typical DL configuration. A numerical simulation with the 3-D finite-difference time-domain (FDTD) method was applied to the broadband DL tool to obtain the wavefield and responses of the receiver. By monitoring the wave attenuation along the metallic drill collar, the intensity of the GW and loss factor can be determined. The coupling efficiency of the GW can be obtained when the total power emitted from the transmitting antenna is known. Simulation results revealed that the coupling efficiency of the GW changes with the water saturation of the formation and frequency. The simulation also suggest, by installing a slope structure adjacent to the transmitting antenna, the energy coupled into the GW could be reduced at different levels. Finally, the relationship between the received signals' amplitude and GW's coupling efficiency showed the quantified contribution of the GW to the received signa
Keywords: finite-difference time-domain (FDTD); single line waveguide; guided wave; dielectric logging